PENGARUH HEDONIC SHOPPING VALUE DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING PELANGGAN BELANJA ONLINE (STUDI PADA MASYARAKAT NAGARI BATUHAMPAR KECAMATAN AKABILURU) - Anada, Aprilia Dwi; Harfandi, Harfandi (Journal of Management Review, 2025)
This research is based on problems that occur in the Nagari Batuhampar Community, Akabiluru District who do online shopping, where there is the behavior of people who make sudden purchases, but the goods purchased are not necessarily needed, there are people who make purchases without thinking about the benefits of the products purchased and the public regrets after making a purchase. This research method uses quantitative research where the data in this research is collected through questionnaires. The population in this research is the people of Nagari Batuhampar who have made purchases while shopping online at the marketplace/online shop, the exact number of which is not known. The sampling technique used the lemeshow formula, totaling 96 respondents. Data processing uses statistical tests which are processed using SPSS version 27. A substantial effect of hedonic shopping value on impulse buying is observed in the Nagari Batuhampar community, Akabiluru sub-district, according to research findings (thitun 13.311>ttable 1.661 and a significance value of 0.000 indicates that shopping lifestyle significantly affects impulse buying.3) The influences of hedonic shopping value and shopping lifestyle on impulse buying are statistically significant (ttable 1.661, p < 0.05, fcount 104.396).the 3.09 ftable